PENGARUH DANA OTONOMI KHUSUS (DOK), DANA TAMBAHAN INFRASTRUKTUR (DTI) DAN PERTUMBUHAN EKONOMI TERHADAP INDEKS PEMBANGUNAN MANUSIA DI KABUPATEN/KOTA PROVINSI PAPUA PERIODE 2019-2021. - Giban, Pilipus; Faishal Fadli (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The granting of Special Autonomy for Papua Province is intended to realise justice, uphold the rule of law, respect for human rights, accelerate economic development, improve the welfare and progress of the Papuan people, in the context of equality and balance with the progress of other provinces (DPR, 2013). The objectives of this study are first, to determine the effect of the Special Autonomy Fund on the Human Development Index in the Regency / City of Papua Province in 2019 - 2021. Second, to determine the effect of the Infrastructure Supplementary Fund on the Human Development Index in the Regency / City of Papua Province in 2019 - 2021. Third, to determine the effect of Economic Growth on the Human Development Index in the Regency / City of Papua Province in 2019 - 2021. This research uses quantitative research. The data used is secondary data obtained from photographs, video recordings, objects, graphic documents (tables, notes and minutes). The variables used are Human Development index, Special Autonomy Fund (DOK), Additional Infrastructure Fund (DTI), and economic growth on human development index in Papua Province. The results showed that the Special Autonomy Fund had no effect on the human development index with a probability value of 0.3132. because the special autonomy funds for Papua and West Papua have decreased due to the Covid-19 corona virus pandemic.